Ancilla Calliopeae : ein Repertorium der neulateinischen Epik Frankreichs 1500-1700 - Braun, Ludwig, Dr. phil (Mittellateinische Studien und Texte ;, 2007)
Presents a panorama of about 85 neo-latin epics composed in France during the 16th and 17th centuries. This collection includes historical, biblical and hagiographic poems.